The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2001
DOI: 10.1046/j.1365-313x.2001.2641040.x
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive salicylic acid‐dependent signaling in cpr1 and cpr6 mutants requires PAD4

Abstract: SummarySalicylic acid (SA)-dependent signaling controls activation of a set of plant defense mechanisms that are important for resistance to a variety of microbial pathogens. Many Arabidopsis mutants that display altered SA-dependent signaling have been isolated. We used double mutant analysis to determine the relative positions of the pad4, cpr1, cpr5, cpr6, dnd1 and dnd2 mutations in the signal transduction network leading to SA-dependent activation of defense gene expression and disease resistance. The pad4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
97
0
5

Year Published

2001
2001
2010
2010

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 126 publications
(108 citation statements)
references
References 63 publications
(97 reference statements)
6
97
0
5
Order By: Relevance
“…Previous studies have reported that spontaneous necrotic lesions can appear in dnd1 leaves (Clough et al, 2000;Jirage et al, 2001). Here, our observation further expands our understanding of the dnd1 mutant phenotype.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Previous studies have reported that spontaneous necrotic lesions can appear in dnd1 leaves (Clough et al, 2000;Jirage et al, 2001). Here, our observation further expands our understanding of the dnd1 mutant phenotype.…”
Section: Resultssupporting
confidence: 82%
“…In addition to involvement in pathogenmediated Ca 2+ signaling, CNGC2 has been suggested to participate in the process of leaf development/ senescence (Kö hler et al, 2001). dnd1 mutant plants have high levels of SA and expression of PR1 (Yu et al, 1998), and spontaneous necrotic lesions appear conditionally in dnd1 leaves (Clough et al, 2000;Jirage et al, 2001). Endogenous H 2 O 2 levels in dnd1 mutants are increased from wild-type levels (Mateo et al, 2006).…”
mentioning
confidence: 99%
“…Signi®cantly, pad4 suppressed cpr1-and cpr6-induced resistance to P.s. maculicola ES4326 and P. parasitica Noco2, and SAdependent PR gene expression (Jirage et al, 2001). Also, pad4 partially suppressed cpr5-induced pathogen resistance, but had no signi®cant effect on SA accumulation or PR gene induction.…”
Section: Salicylic Acid Signaling Antagonizes Pdf12 Expression In Cpr6mentioning
confidence: 94%
“…In contrast, eds1 only partially suppresses resistance in cpr5, leading us to conclude that cpr5 expresses both EDS1-dependent and EDS1-independent components of plant resistance. Jirage et al (2001) show in an accompanying paper that the cpr1-, cpr5-and cpr6-conditioned phenotypes have similar requirements for the SA regulatory gene PAD4 as for EDS1. We conclude that EDS1 and PAD4 have similar positions in the cpr-induced signaling cascades.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation